THE INFLUENCE OF CORRUPTION ON GDP IN ASEAN COUNTRIES (2017-2024) - Asty Indra Larasati; Marselina; Dedy Yuliawan (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of corruption control, foreign direct investment (FDI), inflation, and labor force participation rates on the growth of Gross Domestic Product (GDP) of ASEAN countries during the period 2017-2024. Using a quantitative approach with multiple linear regression and panel data, this study also examined the simultaneous influence of these economic factors on GDP. The results show that corruption control, FDI, and inflation have a significant positive influence on economic growth, while labor force participation rates do not show significant influences. Effective corruption control promotes the creation of a better investment climate, which in turn increases foreign investment flows and productivity. FDI makes an important contribution to technology transfer and production capacity building of ASEAN countries. Controlled inflation also plays a role in creating economic stability that supports long-term investment and consumption decisions. This research provides important insights for policymakers in ASEAN to formulate more effective development strategies by taking into account interrelated macroeconomic factors.